2020
DOI: 10.29267/mxjb.2020.5.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin biosynthesis by Pseudomonas aeruginosa using a biodiesel by product

Abstract: By-products of biodiesel production, such as crude glycerol, require options for their valorization, which allow obtaining high value products with application in several areas. To achieve this, the use of crude glycerol for the production of pyocyanin was analyzed using three strains of Pseudomonas aeruginosa, to increase the concentration of metabolite and compare it with that produced using lysogeny broth (LB medium). The effect was dependent on the strain used, shown positively by only two strains. The phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, pyocyanin remains a costly reagent (e.g., €118 for 5 mg on Merck website). Therefore, the production of pyocyanin is optimized by many research groups by adjusting process conditions, genetic engineering of the microorganisms, or the addition of various substances to the medium, including nanomaterials (Sismaet et al 2014;El-Fouly et al 2015;Ozdal 2019;Ozdal et al 2019;Bacame-Valenzuela et al 2020;da Silva et al 2021;Elbargisy 2021). The analysis of the literature shows that most of the data concerning the influence of nanomaterials on pyocyanin production indicate the inhibition of pigment production.…”
Section: Introductionmentioning
confidence: 99%
“…However, pyocyanin remains a costly reagent (e.g., €118 for 5 mg on Merck website). Therefore, the production of pyocyanin is optimized by many research groups by adjusting process conditions, genetic engineering of the microorganisms, or the addition of various substances to the medium, including nanomaterials (Sismaet et al 2014;El-Fouly et al 2015;Ozdal 2019;Ozdal et al 2019;Bacame-Valenzuela et al 2020;da Silva et al 2021;Elbargisy 2021). The analysis of the literature shows that most of the data concerning the influence of nanomaterials on pyocyanin production indicate the inhibition of pigment production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is feasible that P. aeruginosa NEJ01R produces enzymes to degrade the high volume of polysaccharides present in nejayote RE fraction with a positive effect on PYO production. Different strains of P. aeruginosa have demonstrated biosynthesis capacity for effluents of biotechnological processes (with complex composition) such as biodiesel production [ 16 ]; raw substrates, such as cottonseed meal, grape seeds, pea pods, taro leaves and olive wastes, hydrolyzed by acids [ 5 ]; and others, such as ground corn kernels, ground soybean seeds, potato cooking water, ground watermelon seeds and groundnut [ 17 ]. Different concentrations of PYO can be obtained in a defined medium such as nutrient broth and King’s A supplemented with 1% of different raw substrates in submerged fermentations with P. aeruginosa KU-BI02.…”
Section: Resultsmentioning
confidence: 99%
“…Three colonies (NEJ01R, NEJR5 and NEJ03R) were selected because a green coloration was observed in plates. NEJ01R was used in this study because it showed pigment production in 24 h and growth in different substrates [ 16 ]. The strain NEJ01R was characterized using Gram stain (-) and the biochemical test API 20E (bioMérieux) as Pseudomonas aeruginosa .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Pseudomonas aeruginosa has been described as an opportunist pathogen with high virulence factors and bacterial resistance (included in the ESKAPE list) and is considered one of the most aggressive microorganisms associated with several infectious diseases (Alonso et al, 2020). In addition, due to their versatile metabolism, they can be isolated from complex carbon sources such as industrial effluents and gain important attention in ambient processes (Bacame-Valenzuela et al, 2020). An important characteristic of extremophile P. aeruginosa is the production of a redox-active phenazine derivative denoted as pyocyanin as a response to the bacterial exposition under extreme growth conditions, associated with the overproduction of ROS species (Muller & Merrett, 2014;Whooley & McLoughlin, 1982), which is commonly observed by the characteristic greenish-blue coloration.…”
Section: Introductionmentioning
confidence: 99%